How to Write a Movie in 21 Days : The Inner Movie Method - King, Viki (New York : Harper, 2020)
Viki King's Inner Movie Method is a specific step-by-step process designed to get the story in your heart onto the page. This method doesn't just show how to craft a classic three-act story but also delves into how to clarify the idea you don't quite have yet, how to tell if your idea is really a movie, and how to stop getting ready and start. Once you know what to write, the Inner Movie Method will show you how to write it. This ultimate scriptwriting survival guide also addresses common issues such as how to pay the rent while paying your dues, what to say to your partner when you can't come to bed, and how to keep going when you think you can't. How to Write a Movie in 21 days, first published in 1987, has been translated into many languages and has become an industry-standard guide for filmmakers both in Hollywood and internationally. For accomplished screenwriters honing their craft, as well as for those who have never before brought their ideas to paper, How to Write a Movie in 21 Days is an indispensable guide. And Viki King's upbeat, friendly style is like having a first-rate writing partner every step of the way.
Includes index.
Keywords: Motion picture plays -- Technique; Motion picture authorship -- Psychological aspects; Motion picture authorship -- Psychological aspects; Motion picture plays -- Technique